Effects of High Carbohydrate vs. High Protein Pre-exercise Feedings on Psychophysiological Responses to High Intensity Interval Exercise in Overweight Perimenopausal Women - Kotopoulea-Nikolaidi, Maria; Watkins, Emily; Giannopoulou, Ifigeneia (Frontiers in Nutrition, 2019)
Objective: To investigate a) the acute effect of a bout of high intensity interval exercise (HIIE) on mood, cognitive function and blood pressure in overweight perimenopausal women and b) to compare the effects of high carbohydrate versus high protein pre- HIIE feedings on exercise capacity, mood and cognitive function in this population. Methods: Twelve, overweight, perimenopausal women (age; 45.5±2.3 years, body fat; 32.2±2.1%;) completed a bout of HIIE under 3 pre-exercise feedings (HCHO: high-carbohydrate-low-protein; LCHP: low-carbohydrate-high-protein; control: fasted) in a randomised crossover design. HIIE consisted of 4 intervals of 4 minutes walking at 85%-90% of maximum heart rate and 3 minutes recovery. Before and after HIIE, the shortened version of the profile of mood state questionnaire, the exercise - induced feeling inventory questionnaire and 3 cognitive function tests (Stroop test, Shift Stroop test, n-back test) were administered. Blood pressure was measured pre and post-exercise. Following HIIE a performance test to volitional fatigue was conducted. Results: A single bout of HIIE resulted in significant reductions in blood pressure and improvements in cognitive capacity (p<.05). Both the HCHO and LCHP feedings led to significantly longer exercise performance compared to CON (422±71s and 340±46s vs. 240±32s, respectively, p < .01), with a 1.22 fold greater increase in performance time in HCHO compared to LCHP, although not statistically significant (p > .05). Only the HCHO trial improved total mood disturbance and positive engagement 1h-post exercise compared to CON (p<.05). HCHO and LCHP improved physical exhaustion and revitalisation feelings post exercise vs CON (p<.01). Conclusions: A single HIIE session improves cognitive function and blood pressure in overweight perimenopausal women. High-carbohydrate pre-HIIE feedings can result in greater enhancements in mood and positive engagement to exercise and may improve exercise performance compared to a high-protein meal.